Histological evaluation of human pulp capped with light-cured calcium based cements: a randomized controlled clinical trial - Jeya Gopika, G.; Ramarao, Sathyanarayanan; Usha, Carounanidy; John, Bindu Meera; Vezhavendhan, N. (International Journal of Scientific Reports, 2017)
Background: Calcium hydroxide has traditionally been used as the pulp capping material for pulpal exposures in permanent teeth. The tunnel defects in the barrier and the tendency for dissolution, however, fails to provide permanent protection to the pulp. Light curable resin based cements have been introduced to enable a better marginal seal and lesser dissolution. The purpose of this study was to compare and evaluate the response of human pulp following direct pulp capping with the new resin based Calcium silicate (TheraCal LC) and Calcium hydroxide with hydroxyapatite (Septocal LC) cements compared with calcium hydroxide (Dycal). Methods: 72 intact human premolars scheduled for orthodontic extractions were exposed to direct pulp capping procedures using three different pulp capping agents. Teeth were randomly divided into 3 groups, Group A: Dycal, Group B: TheraCal LC, Group C: Septocal LC. The teeth were extracted at the end of 15 and 40 days’ and were evaluated histologically. They were scored for reparative dentin formation and inflammatory response. Inferential statistics was done using Chi square test. Results: Majority of the specimens in all three groups at the end of 15 days’ showed partial to lateral deposition of hard tissue. There was continuous deposition of hard tissue and severe inflammatory response at the end of 40 days’ in Dycal. There was partial deposition of hard tissue and reduced inflammatory response at the end of 40 days’ in TheraCal LC and Septocal LC. However, the results were not statistically significant between the three groups at two different time periods. Conclusions: Light cured, Calcium silicate (TheraCal LC) and Calcium hydroxide with hydroxyapatite (Septocal LC) cements were as effective as calcium hydroxide (Dycal) in inducing the formation of reparative dentin and evoking inflammatory response.